Pemanfaatan Benda Konkret dalam Pembelajaran Volume Bangun Ruang untuk Meningkatkan Pemahaman Siswa SD - Elisabeth Kezia Tampubolon; Elvi Mailani; Nur Rarastika; Morina Abelita Br Ginting; Gita Rismayani (CV.ITTC INDONESIA, 2025)
This study was conducted to determine the extent to which the use of concrete objects can help students understand the concept of volume, and how it affects student engagement and motivation to learn. This study aims to examine the use of concrete objects in learning the volume of spatial figures as an effort to improve the understanding of elementary school students. This study uses a qualitative descriptive approach. The subjects in this study were elementary school students. Data Collection Techniques used by researchers are Literature Review and Supporting Documents. The results show that the use of concrete object media in mathematics learning has proven effective in improving understanding of the concept of volume of spatial figures and encouraging active student participation in the learning process. Students become more motivated, dare to ask questions, and are able to understand abstract concepts gradually through direct experience and teacher guidance.